The social movement against hate speech for a decade: Legacies from other movements and new strategies - Löschke, Ayaka (British Association for Japanese Studies (BAJS) Conference 2022, 2022)
While the regulation of hate speech has been one of the most important social issues for the last decade in Japan, one of the most important factors which has contributed to the decline of far-right activism, the social movement against hate speech, has not been sufficiently investigated. Shaw (2019, 2020) examines the Japanese Antifa activists, focusing on their relations to the New Left movements that had been established since the 1970s, and their (sub-) cultural backgrounds. Hatano (2021) explains how the understanding of international law reinforced the social movement against hate speech. Higuchi (2020) investigates into the policy-making process of the 2016 Hate Speech Law to which the participants in the movement against hate speech have contributed significantly. However, no scholar has yet asked why the social movement against hate speech could keep its strength for a decade in spite of the fact that most of the participants did not aim for organizational maintenance. Based on the results from 70 interviews which were conducted mainly in Shinjuku, Kawasaki, Kyoto, and Osaka between 2016 and 2021, this presentation analyzes the movement against hate speech, focusing on 1) personal ties, 2) financial power, and 3) access to local and national politicians. I argue that this movement is a crystallization of legacies from different social movements which include not only the Post-Fukushima anti-nuclear movement, but also the movement for local foreign suffrage in Kawasaki and the Buraku liberation movement. Moreover, this presentation points out that the movement’s strategy to lobby not only the opposition, but also politicians from the ruling party differs significantly from Post-war social movements in Japa